PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DI SEKITAR HUTAN ADAT TAWANG PANYAI DI DESA TAPANG SEMADAK KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Sulatri, Desi; Roslinda, Emi; Mariani, Yeni (JURNAL HUTAN LESTARI, 2019)
The abundant biodiversity in the Tawang Panyai Indigenous Forest area has a variety of tree species including timber producers, fruit-producing trees, rattan, bamboo and medicinal plants that are used by communities around indigenous forests. The aims of this study were to documented the use and knowledge of medicinal plants by people around the Tawang Panyai Indigenous Forest in Tapang Semadak Village, Sekadau Hilir District, Sekadau District. The method used in this study was survey method with data collection techniques, namely Purposive sampling conducted semi-structured interview techniques using questionnaires and field observations. The results of the study in Tapang Semadak Village, Sekadau Hilir Subdistrict, Sekadau District, towards 248 respondents obtained by respondents who used medicinal plants were women. Most of the respondents worked as farmers due their education level are still very low, so the majority chose to garden and cultivate. Adults and elderly respondent are more have knowledge of medicinal plants than others. The majority of the religious community is Catholic with Dayak tribe De'sa. The results of the study in the field found 52 types of medicinal plants grouped into 33 families. The plant of family that is widely used is zingiberaceae, based on the most widely used habitus level which is 17 species (32.08%), based on the form of the herb that is widely used is a single herb which is 49 species (92%), based on plant the most widely used drug is leaves, which are 31 species (58.49), based on the method of medicinal plants the most widely used is boiled, namely 27 species (49.06%), based on the method of use that is widely used is by drinking that is 29 species (54.72%), based on the type of disease that is widely used is internal disease, which is 32 species (62.26), based on plants that are found mostly in the traditional forest of Tawang Panyai and home gardens.Keywords: Â Medicinal Plants, Tawang Panyai Customary Forest, Utilization